2018
DOI: 10.1016/j.jid.2018.03.339
|View full text |Cite
|
Sign up to set email alerts
|

333 Influence of social media on cosmetic procedure interest

Abstract: Social media is increasingly cited in plastic surgeon surveys as a reason for undergoing cosmetic procedures, especially non-invasive procedures like onabotulinumtoxinA (Botox) and dermal fillers. We explored trends between social media usage and public interest in cosmetic procedures, as well as how these effects differ by procedure and by specialty (dermatology or plastic surgery). Google Trends was queried for search terms and compared with aggregate user data from Instagram and Facebook. Search terms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…A study reviewing Google search trends found that interest in noninvasive procedures is increasing over time and may be in part driven by social media. 14 In our results, fewer questions were related to surgeon recommendations or cost. Patients may use Realself for general questions but seek out physicians by their geographical proximity or by referrals from friends or family.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A study reviewing Google search trends found that interest in noninvasive procedures is increasing over time and may be in part driven by social media. 14 In our results, fewer questions were related to surgeon recommendations or cost. Patients may use Realself for general questions but seek out physicians by their geographical proximity or by referrals from friends or family.…”
Section: Discussionmentioning
confidence: 51%
“…A study reviewing Google search trends found that interest in noninvasive procedures is increasing over time and may be in part driven by social media. 14…”
Section: Discussionmentioning
confidence: 99%
“…As in the present case controlling for the false discovery rate was more important than the conservative control of familywise error rate, this post-hoc approach appeared adequate (Benjamini and Hochberg, 1995). Based on the recommendations and prior studies, this post-hoc method is strongly recommended if the number of tests is high and it is broadly used in numerous recent studies that conducted similar, large-scale multiple comparisons (Nakajima et al, 2019;Hopkins et al, 2020;Maroun et al, 2021).…”
Section: Analytic Strategymentioning
confidence: 74%
“…Google+ 2018 United States Hill et al [36] Study shows the influence of social media on cosmetic procedure popularity as measured by Google Trends. All 2020 United States Hopkins et al [37] Study shows the importance of cultural considerations in patient healthseeking behavior on social media. WeChat 2020 United States Tan et al [38] Study shows the role of social media in dermatologist selection by patients.…”
Section: Instagram 2022mentioning
confidence: 99%